Causes of mortality and severe morbidity requiring euthanasia in captive Tasmanian devils (Sarcophilus harrisii) in Tasmania. Issue 4 (27th March 2019) - Peck, SJ; Michael, SA; Knowles, G; Davis, A; Pemberton, D
Abstract : Background: Devil facial tumour disease (DFTD) is a contagious cancer causing marked population declines in wild Tasmanian devils. In response to this threat, a captive insurance population has been established. This study investigated causes of death in captive Tasmanian devils. Methods: Clinical and laboratory records of captive Tasmanian devils held in seven Tasmanian captive facilities were analysed for cause of death or severe morbidity requiring euthanasia. Results: Neoplasia was found to be the most common cause of mortality/severe morbidity, accounting for 27/63 of deaths. Cutaneous lymphoma was the most frequently observed tumour (10/27), at a higher incidence than previously reported. The most common cause of severe morbidity, following neoplasia, was leucoencephalomyelopathy, which caused severe, progressive hindlimb paresis and ataxia. Conclusion: Neoplasia, specifically cutaneous lymphoma, and degenerative neurological conditions are the most frequent causes of death in captive Tasmanian devils in Tasmania. Further work to determine the aetiologies of these conditions, as well as effective treatments, would be valuable.